Towards nickel single atom catalyst supported by carbon papers for urea oxidation - Mengfei Li (2022)
In this work nickel nanoparticles supported by carbon paper (NiNP/CP) were prepared by pulsed laser deposition with deposition time of 10s, 30s and 60s in argon atmosphere. In addition, Ni single atoms based on carbon paper (NiSA/CP) with deposition time of 2s, 5s, 10s and 20s were prepared in vacuum. All the samples were tested as catalysts for urea oxidation. The surface and morphology of the nickel catalysts were characterized using scanning electron microscopy and transmission electron microscopy. The urea oxidation reaction of NiNP/CP in KOH solution was investigated by cyclic voltammetry, chronoamperometry and electrochemical impedance spectroscopy. The results showed that the electrodes were catalytically active for urea oxidation, and the ones with less Ni nanoparticles had higher peak current densities. All samples had good stability. The same characterization method was applied to NiSA/CP and it was found that the longer the deposition time, the less ESA of the electrode, but the higher the peak current density, the faster the electron transfer rate, the higher the electrocatalytic activity and the better stability. The results obtained in this work indicate that pulsed laser deposition can be an alternative method for catalyst preparation by depositing metallic nanoparticles or single atoms. As such, they have great potential for practical application as catalysts for the electro-oxidation of urea in the treatment of urea-rich wastewater, and the hydrogen produced in this process can be used for clean power generation